Robot Lengan Pemindah Barang Berbasis Pengolahan Citra Warna - Karitas Darson; Abd. Rabi’; Yandhika Surya Akbar Gumilang (Fakultas Teknik, 2023)
The process of sending goods by humans can consider several factors, namely the weight of the goods, the amount of goods, the length of the trip and the required human labor. The heavier and more goods or the farther the distance that must be traveled, the more human power is needed to move the goods. In addition, the impossibility of human work for 24 hours is also a factor that affects the efficiency and quality of the operation. From these problems, we need a robotic arm for moving goods based on image processing. Where in the early stages it starts with collecting color data on objects using a Raspberry Pi camera which will be processed by the Raspberry Pi 3b for data to be sent to Esp32 and will be forwarded to the servo control as a tool that drives the servo motor as the main mover on the robot arm.. Keywords: Color,Image Processing, Robot Arms